2015
DOI: 10.1111/maq.12223
|View full text |Cite
|
Sign up to set email alerts
|

To Be Free and Normal: Addiction, Governance, and the Therapeutics of Buprenorphine

Abstract: Methadone maintenance has dominated opiate addiction treatment in the United States for decades. Since 2002, opiate addiction has also been treated in general medical settings with a substance called buprenorphine. Based on interviews and participant observation conducted in northern California, this article analyzes how discourses of freedom and normalcy in patient and provider narratives reflect and affect experiences with this treatment modality. I discuss how buprenorphine treatment, in contrast to methado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…Ethnographers of addicted patients and their doctors have found that their relationships are often laden with mutual mistrust, feeding patients' fears of stigmatization and mistreatment (Merrill et al 2002), and that a narrow biomedical concept of addiction that ignores the social processes and power relations that underlie addiction stigma can paradoxically enhance stigma (Hansen and Skinner 2012;Kaye 2012). Nevertheless, other ethnographies have found that individuals on buprenorphine maintenance treatment experience greater autonomy and a heightened sense of ability to lead "normal" lives closer to that of individuals without substance dependence (Harris 2015). Class and geography are important factors, along with race, that ethnographers have shown to shape perceptions of substance dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnographers of addicted patients and their doctors have found that their relationships are often laden with mutual mistrust, feeding patients' fears of stigmatization and mistreatment (Merrill et al 2002), and that a narrow biomedical concept of addiction that ignores the social processes and power relations that underlie addiction stigma can paradoxically enhance stigma (Hansen and Skinner 2012;Kaye 2012). Nevertheless, other ethnographies have found that individuals on buprenorphine maintenance treatment experience greater autonomy and a heightened sense of ability to lead "normal" lives closer to that of individuals without substance dependence (Harris 2015). Class and geography are important factors, along with race, that ethnographers have shown to shape perceptions of substance dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this emphasis on the materiality of implementation practices also helps attune research to the onto-political effects that intervention translations can generate (Law 2004, Mol 2002. Methadone and drug intervention effects, for instance, affect a particular kind of body, making-up a particular kind of subject, normalising a particular kind of conduct, in relation to a particular kind of problem, according to a particular implementation context (Bourgois 2000, Dennis 2016, Fraser 2006, Harris 2015, Keane 2013, Malins 2004, Nettleton et al 2013, Valentine 2007. Taken together, we can ask what methadone treatment translations perform in the context of Kyrgyz prisons: What bodies and subjects do they make?…”
Section: Approachmentioning
confidence: 99%
“…Hence, patients did not have the same long, complicated history with methadone as their counterparts in the United States, where local history had generated many negative experiences of both patients and providers. Therefore, I argue, when buprenorphine was introduced in the United States in 2002, the medication's "social" contexts and effects in particular were often compared with those of methadone and considered more "favourable" (Harris, 2015) as a result.…”
Section: Compulsory Transfersmentioning
confidence: 99%
“…Second, the material connection to the clinic, which Meyers (2014) called "a spatial locus of therapeutic promise" (p. 188), differs across the globe. In the United States, methadone was distributed in stigmatised and racialised clinics, while buprenorphine was marketed as "GP friendly", a doctor's-officebased treatment (Bourgois, 2000;Hansen & Roberts, 2012;Harris, 2015;Netherland, 2011). In Norway, however, methadone treatment, despite patients' criticism, was often distributed through pharmacies and never acquired this type of negative connotation.…”
Section: Compulsory Transfersmentioning
confidence: 99%
See 1 more Smart Citation